Cryptocurrency adoption in Malaysia: Does age, income and education level matter? - Yeong, Y.-C. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Dated back in 2008, the first blockchain-powered cryptocurrency-Bitcoin was introduced by Satoshi Nakamoto. Over the years, the types of cryptocurrencies available in the market amounted to more than 2,000. With the disruptive potential to revolutionize the traditional financial services, cryptocurrencies become a topic of interest among scholars, global regulators, investors, business operators, information technology enthusiasts and consumers. Nevertheless, the negative activities associated with cryptocurrencies such as money laundering and illicit trading, have resulted in the legality of cryptocurrencies remain controversial in the global context.As the worldwide regulators expressed different stance towards cryptocurrency acceptance and adoption, this study sought to gauge the individualâs behavioral intention to use cryptocurrency. Recognizing the dearth of study in Asian countries, especially the developing country, this study addresses the literature gap by focusing the case of Malaysian individuals. Specifically, this study investigated the effects of age, education level and income level differences in an individualâs behavioral intention to use cryptocurrency. The sample is made up of 176 Malaysian individuals who are equipped with cryptocurrency knowledge. The empirical data were gathered using online survey questionnaire via Google form. Subsequently, the data were analyzed using one-way analysis of variance (ANOVA) to understand the demographics effect on the intention to adopt cryptocurrency. Finally, the results revealed that the role of age, education and income level are not significant in influencing an individualâs behavior towards cryptocurrency adoption. Â© BEIESP.